1999
DOI: 10.1111/j.1574-6941.1999.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of bacteria in the mucilage of Microcystis spp. (Cyanobacteria) to benthic and pelagic bacterial production in a hypereutrophic lake

Abstract: The mucilage of cyanobacteria represents a unique habitat for both water column and sediment bacteria. In Lake Vallentunasjön, Sweden, the pelagic Microcystis‐associated bacteria constituted 19–40% of the total bacterial abundance, and their contribution to the total bacterial production was 7–30%. In the sediment, the mucilage bacteria constituted only 1–5% of the total bacterial abundance, but contributed with 8–13% to the total bacterial production during the summer. Microcystis‐associated bacteria thus wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
49
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 34 publications
(52 reference statements)
5
49
0
Order By: Relevance
“…When the intracellular phosphorus content of M. aeruginosa was luxury, it grew by utilization of the intracellular phosphorus in its lag and exponential phases (Okada & Sudo, 1982), thus, only 20% of intracellular phosphorus was released form M. aeruginosa to aqueous solution and to Pseudomonas. However, M. aeruginosa released a lot of phosphorus in its stationary and decline phases while it could simultaneously provide Pseudomonas with organic carbon and trace elements (Sommaruga & Robarts, 1997;Worm, 1998;Brunberg, 1999). Thus, the growth of Pseudomonas was better and the assimilated phosphorus was more when M. aeruginosa was in decline phase than that in stationary phase.…”
Section: Discussionmentioning
confidence: 92%
“…When the intracellular phosphorus content of M. aeruginosa was luxury, it grew by utilization of the intracellular phosphorus in its lag and exponential phases (Okada & Sudo, 1982), thus, only 20% of intracellular phosphorus was released form M. aeruginosa to aqueous solution and to Pseudomonas. However, M. aeruginosa released a lot of phosphorus in its stationary and decline phases while it could simultaneously provide Pseudomonas with organic carbon and trace elements (Sommaruga & Robarts, 1997;Worm, 1998;Brunberg, 1999). Thus, the growth of Pseudomonas was better and the assimilated phosphorus was more when M. aeruginosa was in decline phase than that in stationary phase.…”
Section: Discussionmentioning
confidence: 92%
“…The weaker colonyinducing effect may be due to axenic culture of M. aeruginosa used in the experiment. It is well known that the mucilage keeps the typical shape of a Microcystis colony and colonies of Microcystis in eutrophic lakes are commonly found with numerous bacteria embedded in the mucilage (Bostro¨m et al, 1989;Brunberg, 1999). It is likely that the colony formation of this species in natural water is also associated with other factors such as bacteria may give an advantage to M. aeruginosa to maintain colony mucilage (Brunberg, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the mucilage keeps the typical shape of a Microcystis colony and colonies of Microcystis in eutrophic lakes are commonly found with numerous bacteria embedded in the mucilage (Bostro¨m et al, 1989;Brunberg, 1999). It is likely that the colony formation of this species in natural water is also associated with other factors such as bacteria may give an advantage to M. aeruginosa to maintain colony mucilage (Brunberg, 1999). In addition, various abiotic factors of the field environment, such as temperature, light, nutrients, and windinduced turbulence, may also play an important role on colony formation in M. aeruginosa.…”
Section: Discussionmentioning
confidence: 99%
“…To date, research efforts have broadly identified nutrient inputs and temperature as contributing factors in the development of such blooms, but little focus, due primarily to methodological limitations, has been allocated to the study of the cellular physiology and metabolism of the entire bloom community. Not only do bloom-forming organisms such as Microcystis aeruginosa live in competition with other phytoplankton species, they also live in concert with heterotrophic bacteria, which can attach to the mucilaginous matrix produced by M. aeruginosa colonies (15,16). There is a dearth of information concerning the functional role that co-occurring bacteria may play in bloom dynamics, although recent studies suggest that heterotrophs may play an important role in the metabolism of some nutrients (17,18).…”
mentioning
confidence: 96%